The Role of Local Wisdom in the Development of Aquaculture: A Qualitative Approach - Nurul Fadhilah; Naela Mikyalul Faizah; Fitri Arianti Saputri; Amalia Tasya (PT. Anagata Sembagi Education, 2024)
Aquaculture is an important sector in meeting global food needs and maintaining food security, especially in countries with coastal areas. As the largest archipelagic country, Indonesia has great potential in aquaculture that supports domestic food security and exports. However, the sector faces complex challenges such as climate change and environmental degradation. Sustainable management and integration of local wisdom, such as the